Pengaruh Word of Mouth dan Social Media Marketing terhadap Keputusan Pembelian melalui Niat Pembelian - Syaza Safira; Wan Suryani (Universitas Medan Area, 2026)
This study aims to analyze the influence of word of mouth and social media marketing on purchasing decisions through purchase intentions among customers of the Ca'ca Jamur culinary MSME in Tanjung Selamat Village. This study focuses on the problem of suboptimal consumer purchasing decisions, which are suspected to be influenced by the effectiveness of word of mouth and social media marketing, with purchase intentions as a determining factor of consumer behavior based on consumer behavior theory. This study uses a quantitative approach. Data were collected through questionnaires distributed to 96 respondents who had made purchases and were aware of the Ca'ca Jamur promotion, using a purposive sampling technique. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that word of mouth and social media marketing had a positive and significant effect on purchase intentions. Furthermore, purchase intentions were proven to have a positive and significant effect on purchase decisions. In addition, word of mouth and social media marketing also had an indirect effect on purchase decisions through purchase intentions as a mediating variable. These findings indicate that purchase intentions play an important role in bridging marketing strategies with consumer purchasing decisions.